2018
DOI: 10.1016/j.celrep.2018.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for Translation Initiation Factor Pathways during Ecdysone-Dependent Neuronal Remodeling in Drosophila

Abstract: Dendrite pruning of Drosophila sensory neurons during metamorphosis is induced by the steroid hormone ecdysone through a transcriptional program. In addition, ecdysone activates the eukaryotic initiation factor 4E-binding protein (4E-BP) to inhibit cap-dependent translation initiation. To uncover how efficient translation of ecdysone targets is achieved under these conditions, we assessed the requirements for translation initiation factors during dendrite pruning. We found that the canonical cap-binding comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 55 publications
(97 reference statements)
6
39
1
Order By: Relevance
“…Indeed, if eIF3d interaction with the cap was involved, overexpression of the point mutant eIF3d helix11 that is unable to bind the cap, 41 would be expected to induce negative dominant defects, due to the lack of translation mediated by this interaction. 49 However, overexpression of eIF3d helix11 with the nos-Gal4 driver did not induce any defects in embryonic development or Nos protein synthesis (Supplementary information, Fig. S6).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, if eIF3d interaction with the cap was involved, overexpression of the point mutant eIF3d helix11 that is unable to bind the cap, 41 would be expected to induce negative dominant defects, due to the lack of translation mediated by this interaction. 49 However, overexpression of eIF3d helix11 with the nos-Gal4 driver did not induce any defects in embryonic development or Nos protein synthesis (Supplementary information, Fig. S6).…”
Section: Discussionmentioning
confidence: 94%
“…41 (3) In the same line, eIF3d was involved in cap-dependent translational activation of specific mRNAs for neuronal remodeling in Drosophila larvae, in a context where eIF4E is blocked by 4E-binding protein (4E-BP). 49 Other studies have reported the role of eIF3 in promoting cap-independent translation, thus highlighting eIF3 functional versatility in the control of translation. eIF3 was shown to directly bind methylated adenosine m 6 A, in mRNA 5′UTRs to induce cap-independent translation under stress conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, our data suggest that eIF6 is upstream of ecdysone regulation. It has been recently suggested how translation regulation and hormonal signaling are tightly interconnected in Drosophila 40 and, more generally, that translation is a controller of metabolism 41 . Our experiments unveil an inverse correlation between translational capability and ecdysone production.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA translated by ribosomes is capped at the 5 end, and the cap requires recruitment of eukaryotic initiation factors (eIFs) such as eIF4E and eIF4G before they, in turn, recruit the ribosome (Ostroff et al, 2017;Choi et al, 2018;Das Sharma et al, 2019). Some eIFs are even preferentially involved in different stages of dendritic growth and maintenance, such as eIF4A and eIF3, which have been found to be required for dendritic pruning in Drosophila pupae (Rode et al, 2018). Additionally, some ribosomes can directly bind with mRNA using Internal Ribosome Entry Sites (IRES); however, even while skipping the "middle man", they still depend on a whole host of other proteins that assist with initiation, elongation, and termination of the mRNA (Sutton and Schuman, 2005;Genuth and Barna, 2018).…”
Section: Protein Synthesis and Plasticitymentioning
confidence: 99%